The serrated pathway to colorectal carcinoma: current concepts and challenges. Issue 3 (22nd January 2013) - Bettington, Mark; Walker, Neal; Clouston, Andrew; Brown, Ian; Leggett, Barbara; Whitehall, Vicki
<x xml:space="preserve">Abstract</x> Approximately 30% of colorectal carcinomas develop via a serrated neoplasia pathway, named for the pattern of crypts in the precursor polyps. Molecular abnormalities consistently involve methylation of CpG islands [CpG island methylator phenotype (CIMP)] of low degree (CIMP‐L) or high degree (CIMP‐H), and activating mutations of the mitogen‐activated protein kinase pathway components BRAF or KRAS. Microsatellite instability (MSI) of a high level (MSI‐H) is often present, allowing for a molecular classification of serrated pathway carcinoma as: (i) BRAF mutant/CIMP‐H with either a) MSI‐H or b) microsatellite stable (MSS); and (ii) KRAS mutant/CIMP‐L/MSS. Precursor polyps include sessile serrated adenoma (SSA), characterized by proximal location, crypt architectural disturbance, and BRAF mutation. Microvesicular hyperplasic polyp (MVHP) probably precedes the development of SSA, and borderline lesions between MVHP and SSA occur. Cytological dysplasia in SSA portends advanced genetic abnormality and a high risk of progression to carcinoma. The traditional serrated adenoma has a predilection for the left colon, tubulovillous architecture, eosinophilic cytoplasm, and frequent KRAS mutation. Serrated morphology carcinoma is a new World Health Organization subtype with well‐differentiated, mucinous or trabecular patterns. It has frequent KRAS or BRAF mutations and a poor prognosis. This review provides an insight into the histology and molecular mechanisms driving these serrated pathway lesions.